Depression, sleep physiology, and antidepressant drugs - Winokur, Andrew; Gary, Keith A.; Rodner, Shannon; Rae-Red, Carole; Fernando, Antonio T.; Szuba, Martin P. (Depression and anxiety, 2001)
This review summarizes current findings regarding effects of antidepressant compounds on sleep architecture and interprets their clinical relevance. Effects of the major classes of antidepressant drugs on sleep properties are presented, with the antidepressant compounds organized into categories based primarily on their putative mechanism of action. The majority of antidepressant compounds, across several different categories, exhibit robust suppression of REM sleep. Others, such as bupropion and nefazodone, lack REM suppressant effects. Such findings support the idea that critical neurochemical mechanisms involved in the regulation of discrete sleep stages can be elucidated by means of polysomnographic investigations utilizing pharmacologically targeted agents. Clinicians have appreciated the importance of antidepressant drug effects on sleep when considering therapeutic options for patients. While such decisions in the past were based on empirical observations, an increasing amount of information regarding specific effects of different antidepressant drugs on sleep continuity and sleep architecture is available. Thus, clinicians may choose to consider profiles of sleep effects for different antidepressant drugs in the initial selection of an antidepressant compound. Depression and Anxiety 14:19–28, 2001. © 2001 Wiley‐Liss, Inc.